Comparative analisis of different canopy forms of sweet cherry cultivars - Bicskei Deján, Kende; Gonda, István (Acta Agraria Debreceniensis, 2014)
The Hungarian sweet cherry production has been changed significantly in the last decades, which primarily resulted in growing intensity of the orchards. Due to the favourable selling prices of the sweet cherry many growers see good prospects in this fruit. One of the key questions of their success is the choice of the most proper canopy form according to the growing conditions, which facilities the efficient completion of annual technological operations. In new orchards almost exclusively variations of spindle canopies are established, although many other crown forms are used all over the world. From the point of the domestic sweet cherry production it is indispensable to get information about these canopies, and compare with the prevailing crown forms with central axis. In our experiment we compared free spindle and bush canopies in the Horticultural Experimental Farm of the University of Debrecen in 2013. According to our results it can be stated that the bush canopy can be described with more balanced growth, which makes easier to maintain the vegetative and generative balance. Another positive characteristic of the bush canopy is, that the height of the trees is smaller with 50% compared with the free spindle, which makes the pruning and the harvest easier.